Measuring impact: how and why companies can meet demand for responsibility - Hehenberger, Lisa (Henry Stewart Talks, 2023)
Purposeful work, ESG, Green Deal, Just transition, Sustainability reporting, Impact measurement, Alignment and incentive, Sustainability officer, Consulting – DEI, Chief compliance officer